Perbandingan Peramalan Jumlah Penumpang Keberangkatan Kereta Api di DKI Jakarta Menggunakan Metode Double Exponential Smoothing dan Triple Exponential Smoothing - Irma Nurvianti; Budi Darma Setiawan; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Every year the population of DKI Jakarta Province always increases. It requires the government to improve the quality of public transportation. Train is one of public transportation in DKI Jakarta. Train is a transportation that is used as an alternative mode of transportation when going to travel far to avoid congestion in the city. Therefore, it needs to plan the train capacity for custumer satisfaction. The excessive or less passengers will have an impact on the performance of PT KAI, resulting in the need forecasting the number of passengers departure for trains which the result can be used by the local government and PT KAI to improve services. This research uses and compares the accuracy of Double Exponential Smoothing and Triple Exponential Smoothing. This research uses 156 records of number of passengers, from Januari 2005 to December 2017 obtained from the data published by Statistic Indonesia. From the study testing, the smallest MAPE is found in Triple Exponential Smoothing, it is 3,213% with the most optimal parameters are =0,4, =0,4 and =0,1. The MAPE value is under 10%, it means the method can predict very well.